2012
DOI: 10.1001/archsurg.2012.1954
|View full text |Cite
|
Sign up to set email alerts
|

Transanal Endoscopic Microsurgery in Small, Large, and Giant Rectal Adenomas

Abstract: To assess the outcomes of transanal endoscopic microsurgery in small (Ͻ3 cm), large (3-5 cm), and giant (Ͼ5 cm) lesions and compare these with reports of alternative techniques. Design: Data from January 1998 to February 2010 were prospectively collected. Lesions were divided into 3 groups according to the maximum diameter (group A, Ͻ3 cm; group B, 3-5 cm; and group C, Ͼ5 cm) and outcomes were analyzed separately. Setting: Colorectal unit in a single-district general hospital. Patients: Patients diagnosed as h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 44 publications
3
11
1
1
Order By: Relevance
“…The most common complication, rectal bleeding, is in line with the report of Allaix et al [30], who reported a postoperative haemorrhage rate (requiring blood transfusion, endoscopic haemostasis or rectal packing) in 8% of 300 patients [30]. The rate of peritoneal perforation in the present study (15%) is high when compared with the literature, where rates range from 0-10% [25,[27][28][29]31,32], but this is likely to be due to the high proportion (18%) of tumours in the upper rectum. Our aggressive policy of laparoscopic conversion whenever a perforation was suspected allowed safe suturing of the defect, with only four patients requiring a temporary diverting stoma.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The most common complication, rectal bleeding, is in line with the report of Allaix et al [30], who reported a postoperative haemorrhage rate (requiring blood transfusion, endoscopic haemostasis or rectal packing) in 8% of 300 patients [30]. The rate of peritoneal perforation in the present study (15%) is high when compared with the literature, where rates range from 0-10% [25,[27][28][29]31,32], but this is likely to be due to the high proportion (18%) of tumours in the upper rectum. Our aggressive policy of laparoscopic conversion whenever a perforation was suspected allowed safe suturing of the defect, with only four patients requiring a temporary diverting stoma.…”
Section: Discussionsupporting
confidence: 91%
“…In the case of R1 resection of an adenoma, however, we carry out a simple follow‐up with any future action as appropriate, to avoid a TME with its risk of morbidity and dysfunction. This policy has led to the satisfactory long‐term incidence of local recurrence of only 7%, which compares favourably with other reports .…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Este achado ocorreu, talvez, pelo fato de valorizar-se mais intensamente a incontinência e urgência evacuatória, ou talvez, pelo fato de estarem em região anatômica responsável pela continência. A literatura é inconclusiva neste sentido onde lesões mais proximais por vezes complicam mais (68,149) , por vezes são as mais distais que têm tratamento mais dificultoso e complicam mais (50,151) , e em alguns outros casos não chega a ser considerado fator de risco (202) .…”
Section: A Maioria Das Complicações Ocorreu Em 20 Dias Sendo Que Em unclassified